1991
DOI: 10.1103/physreva.44.5194
|View full text |Cite
|
Sign up to set email alerts
|

Experimental, theoretical, and numerical investigation of the homogenization of density nonuniformities in the periodic transport of a space-charge dominated beam

Abstract: The homogenization of a beam with a transversely nonuniform initial density distribution is examined by masking the ouput from a Pierce electron gun into five parallel beamlets, which are then propagated down a channel of periodically spaced solenoid focusing magnets. Experimental measurements, theoretical predictions, and PIC simulations are in excellent agreement for averaged beam quantities such as rms emittance and envelope radius. In addition, the fine-structure characteristic of the nonlinear evolution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 14 publications
(21 reference statements)
0
25
0
Order By: Relevance
“…Figure 3b shows the simulated phase-space structure of a high-density bunch, in particular showing the large radius and momentum ring that are akin to shock wave formation in strongly interacting media. Modelling of a similar initial distribution of cold ions, in one dimension and without the halo formed by reabsorption of spontaneous emission, has also predicted an expanding shock front 13 , but the formation of high-density boundary layers at the collision of the expanding ion shells has not been previously reported 31 . The negligible thermal diffusion of the ions in our experiments allows direct observation of the shells and high-density boundary layers despite the comparatively low density and long timescales.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Figure 3b shows the simulated phase-space structure of a high-density bunch, in particular showing the large radius and momentum ring that are akin to shock wave formation in strongly interacting media. Modelling of a similar initial distribution of cold ions, in one dimension and without the halo formed by reabsorption of spontaneous emission, has also predicted an expanding shock front 13 , but the formation of high-density boundary layers at the collision of the expanding ion shells has not been previously reported 31 . The negligible thermal diffusion of the ions in our experiments allows direct observation of the shells and high-density boundary layers despite the comparatively low density and long timescales.…”
Section: Resultsmentioning
confidence: 86%
“…These layers have an apparent stickiness or adherence, in that the separate rings do not expand through each other, but compress to form collision boundaries. The compression layers have not been observed in studies of merging electron beams 31 , illustrating the insight available through investigation of space-charge effects with cold and heavy ions.…”
Section: Resultsmentioning
confidence: 94%
“…A particular experiment in this connection was the insertion of a five-beamlet mask in a quincunx pattern was used as a measure of the beam emittance. From previous phosphor screen measurements of the evolution of such a configuration 8 it was observed that details of the pattern evolution were a relatively sensitive function of the initial beam emittance. This was used as a method for measuring the beam emittance, as shown for a particular plane, in Fig.…”
Section: The Umer Experimentsmentioning
confidence: 98%
“…Image formation is normally expected at integer multiples of this distance [13]. Notice that the factor on the righthand side is the inverse of the tune depression.…”
Section: -6 064202-6mentioning
confidence: 99%